2018
DOI: 10.1093/biolinnean/bly113
|View full text |Cite
|
Sign up to set email alerts
|

Mouth morphology of the diving beetle Hyphydrus japonicus (Dytiscidae: Hydroporinae) is specialized for predation on seed shrimps

Abstract: Two-shelled organisms, such as bivalves and seed shrimps, protect themselves from external stresses by firmly closing both shells. We found that the diving beetle Hyphydrus japonicus Sharp, 1873 (Dytiscidae: Hydroporinae) larvae frequently prey on seed shrimps. Other predatory aquatic insects have difficulty in capturing seed shrimps owing to the general form of their mandibles. Larvae of H. japonicus bear a projection on the head (the nasale), which is used in conjunction with vertical movements of the mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Alternatively, it is entirely possible that the cerebrum of Hyphydrus (De Marzo, 1979: fig. 47) and other hydroporines, is not in a different position relative to that of other dytiscid larvae, but appears posteriad due to elongation of the anterior portion of the cephalic capsule into the nasale, another structure adapted for specialized feeding habits (Matta, 1983; Friis et al ., 2003; Hayashi & Ohba, 2018). Furthermore, this could also be a result of shortening the posterior region of the cephalic capsule due to a developmental trade‐off for lengthening of the nasale, given an increase in certain structures is known to result in compensatory decreases in other anatomical features (Nijhout & Wheeler, 1996; Moczek & Nijhout, 2004), including those located near the exaggerated trait (Emlen, 2001).…”
Section: Choosing Among Competing Topologies: Reciprocal Illuminationmentioning
confidence: 99%
“…Alternatively, it is entirely possible that the cerebrum of Hyphydrus (De Marzo, 1979: fig. 47) and other hydroporines, is not in a different position relative to that of other dytiscid larvae, but appears posteriad due to elongation of the anterior portion of the cephalic capsule into the nasale, another structure adapted for specialized feeding habits (Matta, 1983; Friis et al ., 2003; Hayashi & Ohba, 2018). Furthermore, this could also be a result of shortening the posterior region of the cephalic capsule due to a developmental trade‐off for lengthening of the nasale, given an increase in certain structures is known to result in compensatory decreases in other anatomical features (Nijhout & Wheeler, 1996; Moczek & Nijhout, 2004), including those located near the exaggerated trait (Emlen, 2001).…”
Section: Choosing Among Competing Topologies: Reciprocal Illuminationmentioning
confidence: 99%
“…The bivalve carapace of ostracods protects against predation, although it can still occur without destroying the valves. Hayashi and Ohba (2018) showed that laterally flattened ostracod species and those without spines seem to be preferred by larvae of predatory diving beetles (see Hayashi & Ohba, 2018-video in Supporting Information Material). The presence of pointed or rounded external structures (helmets, spines) is common in ostracods and important for the identification of species .…”
Section: Functional Traitsmentioning
confidence: 99%
“…Vertical mandible movement is present in aquatic larvae of some Hydrophus beetles [57,58]. The larvae are predators of shelled shrimp and use their specialized head projection in conjunction with mandibles to grasp prey [59]. Despite staggering anatomical diversity of insects, larval dytiscid beetles and hell ants together appear to represent the only two known instances of mandible-on-head contact used in prey capture [59], both appearing with vertically articulating mouthparts.…”
Section: Reportmentioning
confidence: 99%